Australian occupational therapists' knowledge of the purpose, scope, and funding of assistance dogs. (20th September 2021) - Iong, Ka Kei; Bould, Em; Lalor, Aislinn; Callaway, Libby
Abstract: Background: Assistance dogs, considered a form of assistive technology within Australia's National Disability Insurance Scheme (NDIS), can support scheme participants to achieve greater independence. To receive funding, an allied health assessment report (most often from occupational therapists) is required to justify the animal as a reasonable and necessary support. Objectives: Examine Australian occupational therapists' knowledge and perceptions of assistance dogs; NDIS funding of animal supports; and resources considered useful to guide occupational therapy assessment and report writing. Method: An online anonymous survey was developed and distributed via social media channels, an email listserv, and professional association newsletters to Australian occupational therapists. Data were analysed using descriptive and inferential statistics. Inductive content analysis of open‐ended question responses provided additional insights regarding occupational therapists' knowledge, experiences, and information needs in relation to animal supports. Results: One hundred forty‐five completed surveys were received. A majority of participants had limited knowledge regarding the purpose, scope, and funding of assistance dogs. Only 14 participants had made a referral for an assistance dog for an NDIS participant. For the 36 participants who self‐identified as having good or excellent knowledge of one or more types of assistance dogs, benefits included increasing users' independence, confidence, and quality of life. Although participants agreed they had suitable skills to prescribe assistance dogs, greater clarification regarding their role in the NDIS assessment, advisory, and application process was seen as necessary. Conclusion: This research highlighted the need for increased information for occupational therapists regarding the various types of assistance dogs and NDIS funding rules. The provision of NDIS reporting templates, practice guidance, and professional development resources—as well as occupational therapy curriculum for near‐graduate therapists—could enhance knowledge, clinical reasoning, and practice when considering the most appropriate support and whether an assistance dog is both reasonable and necessary based on the person's goals and needs.